HEALTH INIDCATORS FOR 13 AND 14 YEAR OLD RURAL AND URBAN ADOLESCENTS: a study in State Schools in de Santa Cruz do Sul RS (Fiep Bulletin - online, 2015)
This study of explorative-descriptive character, is aimed at comparing the health-related physical aptitude profile of 13 and 14 year old schoolchildren from public schools, in the rural and urban zone of Santa Cruz do Sul.  The 597 subjects of both sexes, are students from the municipal and state educational network, of rural and urban schools in Santa Cruz do Sul  RS. For data collection we applied the package of Brazil Sports Project somatomotor tests (Corporal Mass, IMC, flexibility, abdonminal strength/resistance, upper limb strength/resistance and aerobic resistance). The statistical analysis is descriptive (average and standard deviation), ANOVA and Post Hoc Test by Scheffé. Data shows us that at the analyzed variables, the average of subjects from the rural area is higher than from the urban area, however, there is no significant difference in health-related physical aptitude ratings between the rural and urban zones. With regard to PROESP normative tables, we perceived that at flexibility, abdominal strength/resistance, aerobic resistance the ratings oscillate between weak and reasonable, and at upper limb strength/resistance, the ratings are good. Differently from what we had expected, we concluded that at the investigated group, the health-related aptitude of adolescents from the rural and urban area is similar, which makes us believe that the life context, surrounding conditions and influences should be similar in the two contexts, moreover because the mass communication means, the proximity of the environments, ease of locomotion and access to educational and cultural means are similar in the investigated contexts.
Keywords: health-related physical aptitude of adolescents; urban and rural environment; public schools.